Allergen-induced dermatitis causes alterations in cutaneous retinoid-mediated signaling in mice. - Janine Gericke; Jan Ittensohn; Johanna Mihály; Sandrine Dubrac; Ralph Rühl (PLoS ONE)
Nuclear receptor-mediated signaling via RARs and PPARδ is involved in the regulation of skin homeostasis. Moreover, activation of both RAR and PPARδ was shown to alter skin inflammation. Endogenous all-trans retinoic acid (ATRA) can activate both receptors depending on specific transport proteins: Fabp5 initiates PPARδ signaling whereas Crabp2 promotes RAR signaling. Repetitive topical applications of ovalbumin (OVA) in combination with intraperitoneal injections of OVA or only intraperitoneal OVA applications were used to induce allergic dermatitis. In our mouse model, expression of IL-4, and Hbegf increased whereas expression of involucrin, Abca12 and Spink5 decreased in inflamed skin, demonstrating altered immune response and epidermal barrier homeostasis. Comprehensive gene expression analysis showed alterations of the cutaneous retinoid metabolism and retinoid-mediated signaling in allergic skin immune response. Notably, ATRA synthesis was increased as indicated by the elevated expression of retinaldehyde dehydrogenases and increased levels of ATRA. Consequently, the expression pattern of genes downstream to RAR was altered. Furthermore, the increased ratio of Fabp5 vs. Crabp2 may indicate an up-regulation of the PPARδ pathway in allergen-induced dermatitis in addition to the altered RAR signaling. Thus, our findings suggest that ATRA levels, RAR-mediated signaling and signaling involved in PPARδ pathways are mainly increased in allergen-induced dermatitis and may contribute to the development and/or maintenance of allergic skin diseases.